The diagnostic ability of echocardiography for infective endocarditis and its associated complications. (2nd November 2015) - Vilacosta, Isidre; Olmos, Carmen; de Agustín, Alberto; López, Javier; Islas, Fabián; Sarriá, Cristina; Ferrera, Carlos; Ortiz-Bautista, Carlos; Sánchez-Enrique, Cristina; Vivas, David; San Román, Alberto
Abstract : Echocardiography, transthoracic and transoesophageal, plays a key role in the diagnosis and prognosis assessment of patients with infective endocarditis. It constitutes a major Duke criterion and is pivotal in treatment guiding. Seven echocardiographic findings are major criteria in the diagnosis of infective endocarditis (IE) (vegetation, abscess, pseudoaneurysm, fistulae, new dehiscence of a prosthetic valve, perforation and valve aneurysm). Echocardiography must be performed as soon as endocarditis is suspected. Transoesophageal echocardiography should be done in most cases of left-sided endocarditis to better define the anatomic lesions and to rule out local complications. Transoesophageal echocardiography is not necessary in isolated right-sided native valve IE with good quality transthoracic examination and unequivocal echocardiographic findings. Echocardiography is a very useful tool to assess the prognosis of patients with IE at any time during the course of the disease. Echocardiographic predictors of poor outcome include presence of periannular complications, prosthetic dysfunction, low left ventricular ejection fraction, pulmonary hypertension and very large vegetations.